PENGETAHUAN ANAK DALAM RANGKA MEMPERSIAPKAN PEMBELAJARAN TATAP MUKA PASCA PANDEMI - Eriqa Pratiwi; Dinda Rizki Tiara (JEA (Jurnal Edukasi AUD), 2021)
Face-to-face learning has begun with some preparations following existing regulations. The practice involves many parents related to the willingness and readiness of the institution, both teachers and staff. However, the rules and guidelines have not clearly stated before face-to-face learning what children need to do. The purpose of the study is to find out what skills children must have before face-to-face learning. The method used in this research is a literature study through sources related to the research objectives. Based on the study results, it was found that some knowledge is essential for children to know and apply in the implementation of face-to-face learning, such as knowing about Covid-19, considering if you don’t feel healthy, carrying out health protocols and being able to feel safe and comfortable studying at school.